ANALISIS ANTRIAN ANGKUTAN PENYEBERANGAN PELABUHAN MERAK - Ariyo Kurniawan; Sugito Sugito; Yuciana Wilandari (Jurnal Gaussian, 2015)
Marine transportation has an important role on economy and migration from one island to another island. Port is a gateway to enter an area and connecting infrastructure between islands. Merak port as the connector of traffic lanes between Java’s island and Sumatra’s island with Ro-Ro ship. Ro-Ro ship is marine transportation that can load a vehicle rolling on and rolling off the ship with its auto-movement (Roll on Roll off). As a service provider of the Ro-Ro ships, the port of Merak trying to serve Ro-Ro ship as good as possible. Measurement of performance system can be analyzed with direct research in the port. The research is being done by observation and recording of the Ro-Ro ships at the pier port of Merak. Based on the results of the analysis, queue model at the port of Merak is (G/G/5) :(GD/∞/∞). Queuing system simulation and ship docking’s cost analysis can be a reference for the port in optimizing management performance the port of Merak crossing. Keywords: supplemental cost, defined benefit plans, accrued benefit cost.